Gambaran Kelainan Prostat di RSUD Tarakan Periode 2015-2020 - Deby Deby; Wiwi Kertadjaya; Militania Eudora Mappadang (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2022)
Benign prostatic hyperplasia (BPH) and prostate adenocarcinoma are the most common prostate disorders. The complaints found were LUTS complaints and caused a decrease in the patient's quality of life. This study aims to describe the characteristics of patients with prostate disorders such as histopathological description, age, chief complaint, PSA levels, age prevalence of patients based on the main complaint, and the relationship between age and LUTS complaints in patients with prostate disorders at Tarakan Hospital for the 2015-2020 period. This study used a cross sectional design using secondary data from medical records with total sampling technique. The results of the study found that there were 72 patients with prostate disorders at Tarakan Hospital for the 2015-2020 period with the incidence of BPH (51.4%) and prostate adenocarcinoma (48.6%). The age of patients with prostate disorders in BPH and adenocarcinoma of the prostate was dominated by the age group of 60-69 years (30.6%) and (20.8%). Based on the Spearman test, the relationship between age and LUTS complaints was p = 0.455 r = 0.089 and there was no significant relationship between age and LUTS complaints.